Effect of Covid-19 on maternal and child health services utilization in Ghana. Evidence from the National Health Insurance Scheme (NHIS). - Yaw Nyarko Opoku-Boateng; Emmanuel Opoku-Asante; Mylene Lagarde; Edward Nketiah-Amponsah (PLoS ONE)
Introduction Covid-19 has had devastating effect on health systems and health utilization globally. Maternal and newborn care were adversely affected but little or nothing is known about the impact it has caused to it. This study seeks to determine the effect of Covid-19 on healthcare utilization with specifics on Antenatal, Postnatal, Deliveries and Out-patient attendance. Methods The study uses secondary data obtained from the four (4) Claims Processing Centres of the National Health Insurance Authority. Through the use of convenient sampling, a total of 502 facilities were selected for inclusion in the research. The study used a longitudinal claims submitted from a cross-section of health facilities namely Community-Based Health Planning and Services, Maternity Homes, Health Centers, Clinics, Primary, Secondary, and Tertiary Hospitals for Antenatal, Postnatal, Out-patient consultations and Delivery attendances from January 2018 to December 2021. Data before and during the Covid-19 pandemic were compared. Segmented regression analysis as an interrupted time series analysis was employed to assess the effect of the pandemic on utilization of services. Results The results indicate that Covid-19 had a significant impact on healthcare utilization in Ghana. Month-on-month, antenatal and out-patient utilization decreased by 21,948.21 and 151,342.40, respectively. Postnatal and delivery services saw an insignificant monthly increase of 37.76 and 1,795.83 from the onset of the covid-19 pandemic and the introduction of movement restrictions. This decline was observed across all care levels, except for Community-Based Health Planning and Services, which showed a slight increase. Also, the results indicate projected average misses of scheduled antenatal, postnatal, out-patient reviews, and deliveries at 21,037.75, 6,428.23, 141,395.30 and 4,745.63 patients respectively. Conclusion The study reveals that Covid-19 led to a decrease in utilization of healthcare which affected pregnant women and newborn care as well. It was evident from the results that community-based healthcare is more resilient and efficient in delivering healthcare amidst the pandemic. In our quest to achieve Universal Health Coverage by 2030, Ghana's health system should improve on the community-based healthcare system and include technology in its healthcare delivery for the people.